Modelos de negócio das empresas de contabilidade face à disrupção tecnológica: Uma proposta de possibilidades - Marracho, A.; Ferreira, P. A. (RISTI - Revista Ibérica de Sistemas e Tecnologias de Informação/Iberian Journal of Information Systems and Technologies (RISTI), 2022)
The purpose of this investigation is to propose business models for accounting firms (BM), coping with technological disruption, to achieve a realm of possibilities inherent to a pragmatic constructivism. Thus, one must: (1) identify emerging technologies impacting BM attributes; (2) identify the attributes of BM in an environment of technological evolution; (3) identify the key ideas guiding the (re)invention of BM. It analyzes direct data collected through interviews conducted with four companies and indirect data from 50 documents obtained from 30 websites, portals, blogs, YouTube channels and similar platforms. It uses content analysis as a data analysis technique. It presents four main conclusions: (1st) there is no universal BM for accounting firms, but several capable of good execution; (2nd) four generic BM; (3rd) emerging technologies are decisive for BM and (4th) four guiding ideas for the (re)invention of BM were identified: (a) business ecosystem; (b) cloud platforms; (c) value-added services and (d) automation and full digitization.